Perancangan Sistem Informasi Buku Kasus Berbasis Web Pada SMK Multi Media Mandiri Jakarta - Syamsul Bahri; Sopiyan Dalis; Ajfi Al Fauzi (JURNAL TEKNIK KOMPUTER, 2020)
Enforcement of rules and order in schools is one of the important things in order to build the character of discipline in students. One way for schools to enforce regulations is to implement a point system. Where every violation committed by students will be recorded and penalized in the form of points in accordance with the category of violation. Students who already have certain points will get action, either in the form of parents' summons, warning letters, or even expelled from school. But sometimes the authorities record student points for having incomplete, miscalculated, or even missing data, thus hampering the handling of violations when students are at a higher grade level. Therefore we need a web-based system that is integrated with the database to manage student violation point data. This system enables accurate and efficient data storage. The method used in the operation of the application is the waterfall, using data and procedures from the school.